Adjustment of Mathematics Materials Based on STEM Approach to Improve Problem-Solving Skills - Si Ayu Yogi Iswari; Gede Suweken; I Made Ardana (Lembaran Ilmu Kependidikan, 2026)
Background – The integration of STEM (Science, Technology, Engineering, and Mathematics) in education has become an important strategy to prepare students to face global challenges and the demands of the Industrial Revolution 4.0. In vocational education, especially in Pharmacy Vocational Schools, mathematics learning is expected to be more contextual and connected to professional practices so that students can develop analytical and problem-solving skills relevant to the pharmaceutical field. Purpose – This study aims to examine the adjustment of pharmaceutical contextual mathematics material based on the STEM approach in improving the problem-solving abilities of Pharmacy Vocational School students. Method/approach – This study employed a literature review method by analyzing and synthesizing various scientific references related to STEM-based learning, contextual mathematics, and pharmaceutical vocational education published within the last five years. The collected literature was reviewed systematically to identify the implementation, benefits, and challenges of integrating STEM approaches into pharmaceutical mathematics learning. Findings – The findings indicate that the application of mathematics materials integrated with pharmaceutical contexts, such as dosage calculations, formulation of pharmaceutical preparations, and laboratory analysis, significantly improves students’ learning engagement, conceptual understanding, and problem-solving abilities. The STEM approach enables students to connect mathematical concepts with scientific and technological applications in pharmaceutical practice, thereby transforming mathematics from an abstract subject into a practical and meaningful analytical tool. In addition, STEM-based learning encourages critical thinking, collaboration, and active participation among students during the learning process. Conclusions – This study concludes that the integration of STEM-based contextual mathematics materials in Pharmacy Vocational Schools can effectively enhance students’ problem-solving skills and support the development of competencies needed in the pharmaceutical profession. The interdisciplinary STEM approach also helps bridge the gap between academic theory and workplace demands. Novelty/Originality/Value – This study highlights the importance of integrating pharmaceutical contexts into STEM-based mathematics learning in vocational education, particularly in Pharmacy Vocational Schools. The study provides insights into how contextual and interdisciplinary learning can improve students’ understanding, engagement, and readiness for professional practice in the pharmaceutical field.